Temporal dynamics of couples' communication behaviors in conflict discussions: A longitudinal analysis. (September 2019) - Leuchtmann, Lorena; Milek, Anne; Bernecker, Katharina; Nussbeck, Fridtjof W.; Backes, Sabine; Martin, Mike; Zemp, Martina; Brandstätter, Veronika; Bodenmann, Guy
Negative and positive conflict communication predicts long-term relationship satisfaction. However, some studies show harmful effects and others show beneficial effects of negative conflict communication on long-term relationship satisfaction. One reason for the heterogeneous results might be that most studies focused on aggregated behaviors across a conflict interaction but neglected the temporal dynamics within such an interaction. This study examined whether individual initial levels and temporal trajectories of negative and positive communications predict long-term relationship satisfaction, and whether self-efficacy beliefs about clarity of other's feelings (CoF) alter initial levels and temporal trajectories of negative and positive communications. Negative and positive communications were measured based on sequentially coded conflict discussions of 365 couples; self-efficacy beliefs about CoF and relationship satisfaction were measured by self-report questionnaires at baseline and at four annual follow-up assessments. Results revealed that women's initial positive communication predicted higher intercepts of both partners' relationship satisfaction, and stronger decreases in women's negative communication predicted a higher intercept of relationship satisfaction in women. Additionally, less steep decreases in women's trajectories of negative communication predicted greater maintenance in women's relationship satisfaction over time. Additionally, men's self-efficacy beliefs about CoF predicted decreases in men's negative communication, increases in women's negative communication, and higher initial levels of women's positive communication. The current study highlights the relevance of dynamic aspects of partners' communication behaviors.